2015
DOI: 10.1158/0008-5472.can-15-2171-t
|View full text |Cite
|
Sign up to set email alerts
|

The PKC/NF-κB Signaling Pathway Induces APOBEC3B Expression in Multiple Human Cancers

Abstract: Overexpression of the antiviral DNA cytosine deaminase APOBEC3B has been linked to somatic mutagenesis in many cancers. HPV infection accounts for APOBEC3B upregulation in cervical and head/neck cancers, but the mechanisms underlying non-viral malignancies are unclear. In this study, we investigated the signal transduction pathways responsible for APOBEC3B upregulation. Activation of protein kinase C (PKC) by the diacylglycerol (DAG) mimic phorbol-myristic acid (PMA) resulted in specific and dose-responsive in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 47 publications
9
136
0
Order By: Relevance
“…5I and J), which continuously express E6 and E7. We speculate that TEAD-mediated A3B upregulation occurs in the early stages of HPV-induced cervical carcinogenesis, whereas the A3B expression in advanced cancer cells is switched to being dependent on the NF-B pathway, as recently reported for breast cancer cells (15), although this hypothesis awaits further experimental verification.…”
Section: Figsupporting
confidence: 62%
“…5I and J), which continuously express E6 and E7. We speculate that TEAD-mediated A3B upregulation occurs in the early stages of HPV-induced cervical carcinogenesis, whereas the A3B expression in advanced cancer cells is switched to being dependent on the NF-B pathway, as recently reported for breast cancer cells (15), although this hypothesis awaits further experimental verification.…”
Section: Figsupporting
confidence: 62%
“…26 In papillomas, NF-κβ and the axis of ROCK2/FAK/β-catenin 5,6 may contribute to the demise of p53, given both NF-κβ 26 and FAK-associated β-catenin 38,46 inhibit p53 expression. These papilloma data thus link NF-κβ with increased DNA mutations/chromosomal instability 25,39 following p53 loss and associated p21 inhibition 47 [below]; and indirectly link ROCK2-mediated NF-κβ to stromal remodelling 25 thus accounting for effects previously observed on expression of ECM molecules such as tenascin C. 48,49 One consequence of p53 loss leading to an altered matrix may involve downregulated microRNAs, 34 such as miR-200 which regulates cell-cell adhesion molecules 35 and effected ROCK signalling in gastric cancer. 36 Of note, p53-mediated miR-200 expression depended upon AKT levels, 37 consistent with p53 loss driving malignant conversion in trigenic HK1.ras/fos/Pten flx carcinogenesis.…”
Section: Discussionmentioning
confidence: 85%
“…47 Of relevance to K14.ROCK er /HK1.ras 1205 carcinogenesis, p21 overexpression protected NEMO Dhepa animals against DNA damage, 39,41 whereas p21 knockout accelerated hepato-carcinogenesis in bi-genic NEMO Dhepa /p21 null mice, 47 thus implicating NF-κβ in chromosomal damage. 33,39,41,45 Most major consequences of ROCK2 activation alter the tumour microenvironment and establish a context permissive for stage-specific progression. 1,2,13 Previous K14.ROCK er studies demonstrated ROCK-associated collagen deposition resulted in a stiffened ECM and increased tissue rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…a rabbit monoclonal antibody used at a dilution of 1:50 (30). This antibody recognizes both A3B and A3G; however, the two proteins can be distinguished by differential gel migration (30; this study).…”
Section: Verhalen Et Almentioning
confidence: 99%